Why Archaeology Is Necessary for a Theory of Urbanization - Ortman, Scott G.; Smith, Michael E.; Lobo, José; Bettencourt, Luís M. A. (Journal of Urban Archaeology, 2020)
Abstract In recent decades researchers in several disciplines have promoted ‘urban science’ to acknowledge the advantages of multidisciplinary approaches and the expanding ability to collect data for contemporary cities. Although practitioners tend to treat the city as the object of study, in our view the more appropriate focus is the process of urbanization. When framed this way, the archaeological record becomes central to a robust theory of urbanization, and even helps to clarify aspects of urbanization that are difficult to study in a present-day context. In this paper, we illustrate this point by discussing examples where archaeological evidence has clarified and expanded aspects of settlement scaling theory, an approach that was initially developed in the context of contemporary cities but which applies to settlements of all shapes, sizes, and periods.